Subpleural pulmonary nodule marking with patent blue V dye prior to surgical resection - Červeňák, Vladimír; Chovanec, Zdeněk; Berková, Alena; Cimflová, Petra; Kelblová, Martina; Čundrle, Ivan; Hanslík, Tomáš; Resler, Jan; Součková, Lenka; Jankaničová, Natália; Vaníček, Jiří (Frontiers in Oncology, 2024)
Subpleural located pulmonary nodules are perioperatively invisible to the surgeon. Their precise identification is conventionally possible by palpation, but often at the cost of performing a thoracotomy. The aim of the study was to evaluate the success rate and feasibility of the pre-operative CT-guided marking subpleural localized nodule using a mixture of Patent Blue V and an iodine contrast agent prior to the extra-anatomical videoassisted thoracoscopic surgery (VATS) resection in patients for whom the primary anatomical resection in terms of segmentectomy or lobectomy was not indicated.The data of consecutive patients with pulmonary nodules located ≤ 30 mm from the parietal pleura, who were indicated for VATS extra-anatomical resection between 2017 to 2023, were retrospectively reviewed and analyzed. All patients indicated for VATS resection underwent color marking of the area with the pulmonary lesion under CT-guided control immediately before the surgery. The primary outcome was the marking success. Morphological lesion characteristics, time from marking to the surgery, procedure related complications, final histology findings and 30day mortality were analyzed. Additionally, we assessed the association of the successful marking and the patient's smoking history.A total of 62 lesions were marked. The successful marking was observed in 56/62 (90.3%) patients. The median time from the lesion marking to the beginning of surgery was 75.0 (IQR 65.0-85.0) minutes. The procedure related pneumothorax was observed in 6 (9.7%) patients, intraparenchymal hematoma in 1 (1.6%) patient. No statistically significant association of the depth of the subpleural lesion's location, occurrence of complications or time from the marking to surgery and the successful marking was observed. The 30day mortality was zero. No association of smoking and successful marking was observed.The method of marking the subpleural pulmonary lesions under CT-guided control with a mixture of Patent Blue V and iodine contrast agent is a safe and effective method with minimal complications. It provides surgeons the precise visualization of the affected pulmonary parenchyma before the planned extra-anatomical VATS resection.